Parentification, distress, and relationship with parents as factors shaping the relationship between adult siblings and their brother/sister with disabilities - Levante, Annalisa; Martis, Chiara; Del Prete, Cristina Maria; Martino, Paola; Pascali, Ferruccio; Primiceri, Patrizia; Vergari, Massimo; Lecciso, Flavia (Frontiers in Psychiatry, 2023)
According to parentification theory, when the siblings of a brother/sister with disabilities assume parent-like duties, this role-reversal is known as sibling-focused parentification. It has a significant impact on these siblings’ distress and on the quality of their family relationships. 605 Italian adult siblings (19-26 years) of people with disabilities completed the online survey. Measures of siblings’ parentification, distress, quality of family relationships, social support, and perceived benefits of parentification were used. The hypothesized model aims to test, on the target sample, the distress and the quality of relationship with parents as mediators on the interplay between the siblings’ parentification and their sibling-relationship. Additionally, social support and perceived benefits of parentification as protective factors were considered. Results showed that the distress and the low quality of the relationship with parents negatively affected the interplay between the siblings’ parentification and the relationship with their own brother/sister with disabilities. Social support and the perceived benefits of parentification decreased the siblings’ distress levels; the perceived benefits of parentification served as a protective factor for the quality of the relationship with parents. Current findings extend the knowledge regarding the risk and protective factors of the siblings’ mental health when disability occurs in family; additionally, they inform family-based intervention programs which should involve the whole family system for reducing distress and improving the well-being of siblings without disabilities.